Influences of Bacillus subtilis and fructooligosaccharide on growth performances, immune responses, and disease resistance of Nile tilapia, Oreochromis niloticus - Panase, Arporn; Thirabunyanon, Mongkol; Promya, Jongkon; Chitmanat, Chanagun (Frontiers in Veterinary Science, 2023)
The present study investigated the effects of Bacillus subtilis and fructooligosaccharide (FOS) on growth performances, immunity improvement, and disease resistance of Nile tilapia (Oreochromis niloticus). The fish (24.5 ± 1.6 g) were fed a basal diet (G1), diets supplemented with 1 g/kg (G2), 3 g/kg (G3) and 5 g/kg (G4) of FOS as well as diets supplemented with 1x109 CFU/g (G5), 3x109 CFU/g (G6) and 5x109 CFU/g (G7) of B. subtilis for 56 days. After the feeding trial, the complement C3, IL-1β, TNF-α, IFN-γ, hsp70 gene expression in the liver was then analyzed by a quantitative Real-time PCR. Then, fish were infected with Streptococcus agalactiae, and the survival rate was recorded. The results showed that FOS and B. subtilis had no significant effect (P > 0.05) on growth performances and survival rate. Lysozyme activity was significantly greater in the G4, G5, G6, and G7 groups. Also, all fish fed FOS and B. subtilis showed significantly (P < 0.05) higher respiratory burst activity than other groups. The expressions of complement C3, IL-1β, TNF-α, IFN-γ and hsp-70 in the liver were significantly higher for fish fed 5 g/kg of FOS as well as for fish that received any concentration level of B. subtilis (P < 0.05) used in the study. After the S. agalactiae challenge test, the survival rate of fish-fed diets supplemented with FOS and B. subtilis was slightly higher than for the control group. The results indicated that FOS and B. subtilis could stimulate immune responses and immune-related genes in tilapia. However, further investigation of other prebiotics or herbs in combination with B. subtilis is encouraged at molecular levels and screening for beneficial metabolites that may increasingly improve digestive enzymes, growth performances, and health benefits in tilapia. In addition, on-farm experiments are needed.